Sport, culture and society : an introduction - Jarvie, Grant, 1955- (Routledge, 2012)
It is impossible to fully understand contemporary society and culture without acknowledging the place of sport. Sport is part of our social and cultural fabric, possessing a social and commercial power that makes it a potent force in the world, for good and for bad. Sport has helped to start wars and promote international reconciliation, while every government around the world commits public resources to sport because of its perceived benefits. From the bleachers to the boardroom, sport matters. Now available in a fully revised and updated new edition, this exciting, comprehensive and accessib.